2018
DOI: 10.1111/jcpp.12984
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorder symptoms at age 10 predict eating disorder symptoms and diagnoses in adolescence

Abstract: Background: Cross-sectional associations between anxiety disorders and eating disorders (EDs) have been well documented; however, limited research has examined whether symptoms of anxiety disorders are prospectively associated with EDs. Identifying these longitudinal associations can aid in discerning relationships among eating and anxiety disorders and point toward a mechanistic understanding of developmental psychopathology. This study investigated the prospective associations between parent-reported anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
64
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 72 publications
5
64
0
1
Order By: Relevance
“…This conclusion is consistent with those of smaller retrospective studies that have found greater general childhood anxiety (i.e. not specific to any given disorder) in individuals who later developed AN (for review see [12,16]).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This conclusion is consistent with those of smaller retrospective studies that have found greater general childhood anxiety (i.e. not specific to any given disorder) in individuals who later developed AN (for review see [12,16]).…”
Section: Introductionsupporting
confidence: 89%
“…The evidence for a causal influence of worry on both anxiety disorders and AN supports the possibility that anxiety disorders and AN are related due to the two sharing causal risk factors. A recent study probed associations between independent transdiagnostic anxiety disorder factors (measured at age 10) and lifetime AN by age 16, in the same population cohort as that of Study One [16]. In this earlier investigation, a quantitative worry component (derived from a factor analysis, and reflecting worry across multiple domains) predicted AN development, while alternative anxiety disorder components did not.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the same population cohort identified associations of physical anxiety disorder symptoms assessed at age 10 with fasting behaviour at the 13–14 wave (Schaumberg et al, ). We build upon this finding to identify more proximal predictive effects of anxiety disorders on fasting, and effects beyond early adolescence, that is, the mid‐late adolescent period.…”
Section: Discussionmentioning
confidence: 99%
“…A recent investigation observed a prospective association between certain latent anxiety factors, derived from broad anxiety symptoms, with fasting. In this study anxiety disorder pathology was assessed at age 10, and disordered eating behaviour at age 14 (Schaumberg et al, ). Whether the reported associations are maintained over time, and particularly during the mid‐late adolescent period in which AN incidence is highest (Micali et al, ), remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated anxiety was determined by a score of ≥32 on the STAIC trait scale (Spielberger, Lushene, Vagg, & Jacobs, 1983). Lossof-control eating and anxiety are highly correlated cross-sectionally and prospectively (Shomaker et al, 2010;Tanofsky-Kraff et al, 2011) and each construct has been shown to predict excess weight gain (Sonneville et al, 2013;Staiano, Marker, Martin, & Katzmarzyk, 2016;Tanofsky-Kraff et al, 2009) and eating disorders (Schaumberg et al, 2019), specifically binge-eating disorder (Hilbert, Hartmann, Czaja, & Schoebi, 2013;Tanofsky-Kraff et al, 2011).…”
mentioning
confidence: 99%